Amplitude and oscillating frequency of chemically reactive flow along inclined gravity-driven surface in the presence of thermal conductivity - Attia Boudjemline; Zia Ullah; Musaad S. Aldhabani; Hammad Al-Shammari; Essam R. El-Zahar; Laila F. Seddek; Ahmed Alamer (Case Studies in Thermal Engineering, 2024)
The main goal of current research is to elaborate wave oscillations and amplitude of heat mass transfer across gravity-driven surface. The heat and mass transfer through inclined gravity driven shapes is very useful in aeronautical technologies and airspace devices. In low gravitational pressure, the concentrated particles move faster with maximum heating rate. The novelty of present mechanism is to estimate the gravity and primitive modulation of chemically reactive flow of periodic and oscillatory heat and mass transfer across the inclined gravity-driven plate under viscosity and thermal conductivity effects. The viscosity, gravity and conductivity are assumed as temperature dependent. The non-dimensional model is converted into algebraic system using finite difference and primitive approach. The Gaussian elimination technique is used to explore velocity, temperature and concentration profiles for different governing variables. The amplitude of shear stress, oscillatory heat and oscillatory mass transfer is examined numerically and graphically. The oscillatory stokes conditions are used to evaluate oscillatory behavior of physical properties. It is found that the mass concentration increases as viscosity of fluid increases under low gravitational pressure. It is seen that the enhancement in velocity of fluid grows as viscosity of fluid reduces. The increasing amplitude and frequency of heat transmission is drafted at π/6 angle under maximum buoyancy forces. The oscillations in mass and shearing stress enhances as buoyancy force increases under minimum gravity.